2012
DOI: 10.1007/s10534-012-9543-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and adipocyte cells respond differentially to iron overload, hypoxic and inflammatory challenge

Abstract: Adipose tissue secretes numerous pro-inflammatory cytokines, such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α that can lead to insulin resistance (IR). In the liver, both IL-6 and TNF-α induce IR by inhibiting phosphorylation or ubiquitination of IRS1. In IR development, Fe is a risk factor in type-2 diabetes development. We studied the expression of genes related to inflammation, hypoxia, and mitochondrial function in hepatic (HepG2) and adipose (3T3-L1) cells. HepG2 and 3T3-L1 cells were incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…It has been shown that in the presence of iron overload, there is an increase in ER stress, 35 leading to suppression of lysosomal turnover 36 and suppression of autophagy. 37 Our results are in conformity with these observations given that we found a higher expression of genes related to ER stress and decreased expression of genes governing autophagy (ATG7) in patients with ACLF, as compared to cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in the presence of iron overload, there is an increase in ER stress, 35 leading to suppression of lysosomal turnover 36 and suppression of autophagy. 37 Our results are in conformity with these observations given that we found a higher expression of genes related to ER stress and decreased expression of genes governing autophagy (ATG7) in patients with ACLF, as compared to cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy subjects had no history or clinical evidence of previous or present illness. All patients in the ACLF group were managed according to the standard of care, including intensive care monitoring, high-calorie diet (35)(36)(37)(38)(39)(40) cal/kg/day), intravenous albumin, broad-spectrum antibiotics, pentoxifylline for alcoholic hepatitis, antivirals, which included tenofovir for hepatitis B virus (HBV) reactivation, terlipressin for hepatorenal syndrome, and lactulose bowel enemas. In the presence of acute kidney injury, the dose of tenofovir was modified according to creatinine clearance.…”
Section: Methodsmentioning
confidence: 99%
“…Since IO was demonstrated to induce the TNF-α expression that further triggers osteoclastic function (13,22,23), the TNF-α level was measured. Consistent with a previous study (13), the TNF-α level in the IO mice was approximately 1.5-fold higher compared to the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Iron accumulation in tissue is likely to provoke the formation of reactive oxygen species (ROS) (12), while the iron excess is likely to induce an increased expression of tumor necrosis factor-α (TNF-α) (13). However, the contribution of oxidative stress to osteoporosis was also recognized (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Although iron may be described as a powerful trigger of reactive oxygen species and lipolysis, its presence in the medium might de facto hamper IL-6 expression [30]; this is probably because iron entering the cell may create an inhibitory microenvironment for early IL-6 enhancement of gene expression. Although TNF-a leads to oxidative stress and changes in mitochondrial bioenergetics, particularly by decreasing PGC-1a, IL-6 does not appear to have immediate effect on these events, except for late mitochondrial dysfunction [31,32]. It is possible that early gene expression of TNF-a created a progressive increase in oxidative stress, mitochondrial dysfunction, and lipolysis, which later triggered IL-6 gene to be highly expressed [32].…”
Section: Marked Effect On Il-6 Gene Expressionmentioning
confidence: 99%